Comparison of the Effects of Apo(a) Kringle IV-10 and Plasminogen Kringles on the Interactions of Lipoprotein(a) with Regulatory Molecules - Xue, Song; Green, Michael A.; LoGrasso, Philip V.; Boettcher, Brian R.; Madison, Edwin L.; Curtiss, Linda K.; Miles, Lindsey A. (Thrombosis and Haemostasis, 1999)
Lipoprotein(a) [Lp(a)] is associated with atherosclerosis and with disease processes involving thrombosis. Lp(a) contains apoprotein (a) [apo(a)], which has a sequence highly homologous to plasminogen. Hence, Lp(a) binds directly to extracellular matrix, cellular plasminogen receptors and fibrin(ogen) and competes for the binding of plasminogen to these regulatory surfaces. These interactions may contribute to the proatherothrombogenic consequences of high Lp(a) levels. These interactions are mediated by lysine binding sites (LBS). Therefore, we examined the role of apo(a) kringle IV-10 [the only apo(a) kringle demonstrated to exhibit lysine binding activity in the intact lipoprotein] in the interaction of Lp(a) with these regulatory molecules. We have compared directly apo(a) KIV-10 with plasminogen K4 to examine whether these highly structurally homologous kringle modules are also functionally homologous. Futhermore, because the plasminogen K5-protease domain (K5-PD) binds directly to fibrin, we have also examined the ability of this plasminogen fragment to inhibit the interaction of Lp(a) with these regulatory molecules and with extracellular matrix. Apo(a) KIV-10 competed effectively for the binding of 125I-Lp(a) to these surfaces but was less effective than either intact Lp(a), plasminogen K4 or plasminogen. Plasminogen K5-PD was a better competitor than apo(a) KIV-10 for 125I-Lp(a) binding to the representative extra-cellular matrix, Matrigel, and to plasmin-treated fibrinogen. In contrast, plasminogen K5-PD did not compete for the interaction of Lp(a) with cells, although it effectively competed for plasminogen binding. These results suggest that Lp(a) recognizes sites in all of the regulatory molecules that are also recognized by apo(a) KIV-10 and that Lp(a) recognizes sites in extracellular matrix and in plasmin-modified fibrinogen that also are recognized by plasminogen K5-PD. Thus, the interaction of Lp(a) with cells is clearly distinct from that with extracellular matrix and with plasmin-treated fibrinogen and the recognition sites within Lp(a) and plasminogen for these regulatory molecules are not identical.Portions of this manuscript were presented at the 69th Meeting of the American Heart Association, New Orleans, LA 1996.